Current political-epistemic insurgencies in the Americas: left turns, anti-imperial turns, de-colonial turns - Lao-Montes, Agustín (2016)
This article outlines an analysis of the actual worldwide situation, making a general inquiry of the most important epistemic political insurgencies in Latin America. The author presents a series of key questions which must reference the collective task of constructing the decolonial shift as both an epistemic and ethical-political alternative.